The Falkland basins: new structural model and hydrocarbon bearing prospects (by remote sensing and geoelectric data) - Korchagin, I.N.; Bakhmutov, V.G.; Levashov, S.P.; Solovyov, V.D.; Yakymchuk, N.A.; Bozhezha, D.N. (Український антарктичний журнал, 2014)
New results of geoelectric measurements were obtained during the season works of 17 Ukrainian Antarctic Expedition (XVII UAE, 2012). New data on the deep structure of the tectonic zone between the Falkland Islands and the South Shetland Islands make it possible to estimate the probable nature of geodynamic processes in this region. Deep geoelectric boundaries position and nature of their contacts near the South Shetland Islands and the Falkland Islands show a fundamentally different distribution of crustal and mantle layers in the Strait structures with continental and oceanic rock complexes. За матеріалами геоелектричних вимірювань під час сезонних робіт 17 Української антарктичної експедиції (УАЕ) в 2012 р. було отримано нові дані про глибинну будову структур тектонічної зони між Фолклендськими островами на півночі та Південно-Шетландськими островами на півдні. Вони дають можливість оцінити ймовірнісний характер геодинамічних процесів формування та еволюції, що відбувалися в межах цього регіону. По материалам геоэлектрических измерений во время сезонных работ 17 Украинской антарктической экспедиции (XVII УАЭ, 2012 г.) были получены новые данные о глубинном строении тектонической зоны между Фолклендскими островами на севере и Южно-Шетландскими островами рования и эволюции, происходивших в пределах этого обширного региона.